The Evaluation of Hydrogeological Conditions and The Construction of Spatial Sensitivity Maps against Pollution Factors Using Geoenvironmental Variables in Easy Coastal Lattakia Basin (Latakia University Journal -Basic Sciences Series, 2021)
Groundwater Drastic method has been used to examine the potential sensitivity In Lattakia basin that is characterised by the existence of varied human activities and depths of groundwater levels which are close to the surface  using Arc GIS10.5. location the modified Drastic system has been developed by combining the land uses and its divisions with general Drastic model , As a result, the final values of Drastic have been modulated into two categories "low and moderate sensitivity".It has been found that the introduction of the uses of the land and divisions has increasedthe potentiality concerning the moderate sensitivity of  the Groundwater.As a final result, the general content of the sensitivity map which has been established for Lattakia basin showed, the domination of low sensitivity in the north western and the north eastern areas which hare big location depths of the Groundwater and high topographic altitudes. while the moderate sensitivity category dominated in the southern areas of the study region.The research recommended the need to develop a mathematical model for the movement of pollutants in the aquifer system of the Lattakia basin.